Nos encanta el morado! = We love purple! - Little, Richard, 1978-; Vega, Eida de la (New York, NY : Gareth Stevens Publishing, 2016)
Offers an illustrated look at several things that are purple.
"For English-language text: Levels: GR: B; DRA: 2"--Page 4 of cover.
Parallel text in English and Spanish.
Keywords: Purple -- Juvenile literature; Colors -- Juvenile literature; Color -- Juvenile literature; Spanish language materials -- Bilingual -- Juvenile literature